Optic disc shape in patients with long-lasting unilateral esotropia and exotropia - Shang, Kunte; Dai, Yi; Liu, Hong; Qu, Xiaomei; Wen, Wen; Jonas, Jost B. (BMC ophthalmology, 2019)
Horizontal eye movements have been proposed to induce biomechanical stress and strain on optic nerve head. Since strabismus may lead to sustained adduction or abduction, we investigate the effects of long lasting unilateral horizontal strabismus on the morphology of optic disc.
Gesehen am 05.12.2019